Ranma 1/2. [vol. 17-18] - Takahashi, Rumiko, 1957-; Jones, Gerard, 1957-; Yoshida, Toshifumi (Viz Media, 2015)
Meet Picolet Chardin II, master of the tres terrifying La Belle France School of Martial-Arts Dining. It turns out that Ranma's and Akane's fathers - as they've been known to do, once or twice - have promised one of their children in exchange for a debt, and now that debt's come due. If Ranma can't defeat Picolet at his own game, it'd be more than La Belle France -- it'd be wedding bells!